Peran Media Pembelajaran Berbasis Storytelling terhadap Tingkat Pemahaman Siswa Kelas VIII di MTS Misbahul Khair - Ria Sivti Fendi; Ahmad Syafifuddin; Tri Olan Dari; Azizah Azizah; Dessy Kurnia Mulyani (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
To increase efficiency, productivity and wider access to information in teaching and learning activities, the use of technology in the learning process is currently a top priority. However, problems arise when schools lack sufficient technological devices to support technology-based learning. Therefore, there is a need for innovation in creating appropriate and useful learning media. The use of video-based learning media combined with a digital story approach is an alternative to overcome this problem. The question now is whether this learning method is successful in increasing students' interest and knowledge of arts and culture? What learning methods are used to teach using story-based digital media? This research was conducted at MTS Misbahul Khair. Data was collected through questionnaires and observations. The study results show: 1) Digital video-based learning design has been used well. 2) The questionnaire shows that this media is effective; 80% of students say that video-based digital stories increase their interest, focus and understanding. However, there are several obstacles, such as limited specifications for students' digital devices and the need for quite large storage space and internet quota.